2022
DOI: 10.3390/su142113930
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Germination of Malus sieversii (Ledeb.) M. Roem. (Rosaceae) Seeds after Ingestion by Cattle, Horses, and Sheep

Abstract: Livestock can transport seeds long distances by endozoochory due to their large home range and capacity to move among different habitats. However, differences in digestive system and body size between different livestock species may result in variations in the dispersal of domestic livestock. To test such effects, we explore the effects of endozoochorous seed dispersal of Malus sieversii by three livestock: cattle, horse, and sheep in the Ili Botany Garden, northwest of China. We collected seeds of M. sieversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The seed dispersion pattern was estimated by integrating the movement trajectory distribution of cattle during seed retention in the digestive tract after the cattle had consumed fruits [51]. Xu et al (2022) observed that the seeds were no longer detectable in the cattle's feces on the sixth day following the ingestion of M. sieversii seeds [43]. To estimate the dispersal distance of seeds by cattle, we conducted GPS-tracking experiments during the fruiting period of M. sieversii in 2022.…”
Section: Estimation Of Seed Dispersal Distance By Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…The seed dispersion pattern was estimated by integrating the movement trajectory distribution of cattle during seed retention in the digestive tract after the cattle had consumed fruits [51]. Xu et al (2022) observed that the seeds were no longer detectable in the cattle's feces on the sixth day following the ingestion of M. sieversii seeds [43]. To estimate the dispersal distance of seeds by cattle, we conducted GPS-tracking experiments during the fruiting period of M. sieversii in 2022.…”
Section: Estimation Of Seed Dispersal Distance By Cattlementioning
confidence: 99%
“…Additionally, we discovered that the distribution area of M. sieversii is abundant with cattle feces containing its seeds and seedlings (Figure S1). Xu et al (2022) found that recovery rate of intact seeds of M. sieversii seeds after passing through the digestive tract of cattle was as high as 54.05%, and the recovered seed vitality was 100% [43]. However, comprehensive studies on the seed dispersal effectiveness of M. sieversii by cattle are still lacking.…”
Section: Introductionmentioning
confidence: 99%